New Testament verbs of communication: a case frame and exegetical study - Danove, Paul L. (Library of New Testament studies, 2015)
Chapter 1: Introduction to Case Frame Analysis -- Chapter 2: Introduction to Usage, Event, and Semantic Features -- Chapter 3: Oral Communication: Usages ACE C +or -- Chapter 4: Oral Communication: Usages ACE E +or -- Chapter 5: Non-Oral Communication: All Usages ACE or -- Chapter 6: Usages of Events Derived from Communication (ACE) -- Chapter 7: Oral Communication for a Benefactive: All Usages ACEB +or -- Chapter 8: The Active/Middle Distinction with Four Verbs -- Chapter 9: Further Considerations and Conclusion -- Chapter 10: The Case Frame Lexicon and Parsing Guide -- Appendices -- Bibliography -- Index of Authors